2010
DOI: 10.1016/j.pbb.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced locomotor sensitization in DBA/2J mice is associated with alterations in GABAA subunit gene expression and behavioral sensitivity to GABAA acting drugs

Abstract: Repeated exposure to ethanol may produce increased sensitivity to its acute locomotor stimulant actions, a process referred to as locomotor sensitization. Neuroadaptation within certain brain circuits, including those possessing GABAA receptors, may underlie locomotor sensitization to ethanol. Indeed, GABAA receptors are documented mediators of ethanol's cellular and behavioral actions. Moreover, because subunit composition of this receptor is predictive of its pharmacology, it is possible that alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…For example, we have shown similar levels of ethanol sensitization between mice injected repeatedly with ethanol in the test context or in their home cages (Didone et al, 2008). It is also noteworthy that the standard experimental protocol used to study ethanol sensitization in several laboratories involves the repeated administration of ethanol in the home cage and a test session in a different environment (Quadros et al, 2002;Meyer and Phillips, 2007;Linsenbardt and Boehm, 2010). Although these latter studies were not aimed at testing the context dependency of ethanol sensitization, it is clear from their results that the development of a robust ethanol sensitization does not require association with a specific context.…”
Section: Introductionsupporting
confidence: 56%
“…For example, we have shown similar levels of ethanol sensitization between mice injected repeatedly with ethanol in the test context or in their home cages (Didone et al, 2008). It is also noteworthy that the standard experimental protocol used to study ethanol sensitization in several laboratories involves the repeated administration of ethanol in the home cage and a test session in a different environment (Quadros et al, 2002;Meyer and Phillips, 2007;Linsenbardt and Boehm, 2010). Although these latter studies were not aimed at testing the context dependency of ethanol sensitization, it is clear from their results that the development of a robust ethanol sensitization does not require association with a specific context.…”
Section: Introductionsupporting
confidence: 56%
“…Quanitative real-time reverse transcriptase PCR (qPCR) was performed to compare mRNA levels of three GABA A receptor subunits, as previously described (Linsenbardt and Boehm, 2010), across the estrous cycle. The δ and α4 subunits are exclusively expressed by extrasynaptic GABA A receptors, whereas ɣ2 is often found in synaptic GABA A receptors.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been demonstrated that the expression of homer 1A, dopamine D3 receptor, several GABA receptor subunits genes, and immediate early genes such as egr-1 and c-Fos is altered after EIBS (Faria et al, 2008;Harrison and Nobrega, 2009;Linsenbardt and Boehm, 2010;dos Santos et al, 2009). Thus we sought to carry out an exploratory analysis to identify regulations of expression from genes belonging to signal transduction-and epigeneticrelated pathways.…”
mentioning
confidence: 99%